(untitled) (Revista Contexto & Educação, 2026)
The present study aimed to evaluate the perceptions of students enrolled in the Biological Sciences program at Federal University of Alfenas, who were exposed to a repository of Open Educational Resources (OER) developed by a research group consisting of undergraduate students and a master’s student. The materials produced focused on the theme of Respiratory Physiology and were supervised by the faculty member responsible for the Physiology course. A range of digital materials was created and made available in the OER repository, including games, videos, and podcasts. Subsequently, these materials were evaluated by the Biological Sciences students through a qualitative assessment using a questionnaire. The data collected from the questionnaire were analyzed using a descriptive qualitative approach, focusing on the analysis of the responses to the online survey. The results indicated that innovations such as OER are positively perceived by higher education students. Supplementary teaching content in the form of videos and games were particularly favored by the participants. Thus, OER can be considered a valuable tool for enhancing the quality of teaching and motivating students to engage with the subject matter. Furthermore, the use of OER represents a promising strategy for democratizing access to knowledge in a cost-effective manner, while also offering institutions a means to increase student retention and engagement.